Assessing the contribution of managed aquifer recharge programs on groundwater storage in the Ramganga Basin - Alam, Mohammad Faiz; Pavelic, Paul; Sharma, Navneet; Sikka, Alok (Elsevier, 2025)
Groundwater, which supports nearly two-thirds of irrigation and underpins food security in India, faces depletion due to unsustainable abstraction. Managed aquifer recharge (MAR) programs, which replenish aquifers during periods of surplus surface water, have emerged as a national strategy to bolster groundwater security. This study evaluates the contribution of government-led aquifer recharge programs to groundwater storage in the alluvial aquifers of the Ramganga basin, whilst taking account of factors such as climate variability and agricultural water demand. The analysis, drawing on district-level MAR development data, field monitoring of recharge structures, and trends in rainfall, irrigation, and groundwater levels, reveals that MAR initiatives have a positive impact on groundwater storage. However, at their current scale, their contribution is modest accounting for an estimated 2.5–7.5 % of rainfall-recharge in 2023. Thus, groundwater levels continue to decline across districts, with average annual depletion rates of 0.21–0.29 m/year, indicating that current MAR contributions remain insufficient to counter the supply-demand imbalance. Scaling of MAR has been assessed to require >40,000 additional recharge ponds. Moreover, the recharge efficiency of existing structures, averaging 48 mm/day, falls well below that of optimized MAR systems that incorporate recharge wells. Beyond supply-side measures, this study highlights the need for integrated demand management strategies in the Ganges basin. It underscores the pressing need for a comprehensive, science-based approach to MAR implementation, coupled with demand-side interventions, to ensure sustainable groundwater management.